THE EFFECTIVENES OF GIST STRATEGY BASED ON LOCAL WISDOM TOWARD READING COMPREHENSION OF STUDENT'S NARRATIVE TEXT'S - Islam, Aang Fatihul; Sonagar, Yunansa (STKIP PGRI Jombang, 2023)
Reading comprehension is a crucial skill that students must master to understand texts effectively. Choosing the proper techniques for teaching reading and making lessons attractive and effective are essential factors determining the success of the learning process in education. This study aims to know whether the student reading narrative text with the gist strategy achieves better than students reading the narrative text without using the gist strategy. A total of 60 students consisting of two classes (a control class and an experimental class) at SMK PGRI 1 Jombang participated in this study. The design of quasi-experimental was used in this study. This research used test instruments (pre-test and post-test) with multiple-choice questions using Google Forms. This study revealed a significant difference (p-value 0,011) in student learning outcomes scores in the experimental and control classes. Pertaining to this, schools can improvise the curriculum by applying GIST in certain learning subjects to improve student understanding.